2016
DOI: 10.1080/09540121.2016.1192100
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of quality of life among Cambodian adults living with HIV/AIDS and using antiretroviral therapy: a short report

Abstract: The aim of this study was to evaluate quality of life (QOL) and analyze its determinants among Cambodian adults living with HIV/AIDS who are on antiretroviral therapy (ART). A cross-sectional study was conducted using convenience sampling to select 150 adults 18 years of age or older from the patient population at the HIV/AIDS care hospital in Phnom Penh, Cambodia. QOL was assessed using the World Health Organization Quality of Life HIV BREF; socio-demographic characteristics, time elapsed since HIV diagnosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
1
11
0
4
Order By: Relevance
“…O domínio espiritualidade, religião e crenças pessoais contém quatro facetas e apresentou valor médio limítrofe entre intermediário e superior, sendo a segunda maior média entre os domínios. A classificação como intermediário corrobora com os achados em Macaé 3 , em Rio das Ostras 13 , na África do Sul 33 e no Camboja 34 . Os dados na Nigéria 24 e São José 31 obtiveram avaliação superior e, em Mossoró 32 teve média abaixo de dez, sugerindo avaliação inferior da qualidade de vida.…”
Section: Domínios Do Whoqol-hiv Brefunclassified
See 2 more Smart Citations
“…O domínio espiritualidade, religião e crenças pessoais contém quatro facetas e apresentou valor médio limítrofe entre intermediário e superior, sendo a segunda maior média entre os domínios. A classificação como intermediário corrobora com os achados em Macaé 3 , em Rio das Ostras 13 , na África do Sul 33 e no Camboja 34 . Os dados na Nigéria 24 e São José 31 obtiveram avaliação superior e, em Mossoró 32 teve média abaixo de dez, sugerindo avaliação inferior da qualidade de vida.…”
Section: Domínios Do Whoqol-hiv Brefunclassified
“…O domínio físico contém quatro facetas e teve avaliação intermediária, semelhante aos achados na África do Sul 33 , Camboja 34 ; e no Brasil, em Fortaleza 12 e Mossoró 32 . Já os resultados em São José 31 e na Nigéria 24 apontaram escores sugestivos de avaliação superior.…”
Section: Domínios Do Whoqol-hiv Brefunclassified
See 1 more Smart Citation
“…Previous research on the relation between gender and HRQoL of PLH had mixed results. Some studies reported that mental HRQoL of male PLH was better than that of female PLH [42], while others generated opposite results [8, 13]. Other research showed no apparent correlation between gender and HRQoL [10].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, family factors play an essential role in the HRQoL of PLH in Asia because of the cultural norms with strong family values [12]. Family income [13] and family support [14] were the associating factors identified in previous studies, as family presents a source of support for the individual with HIV/AIDS, contributing to their physical and mental well-being [5]. Therefore, the study of PLH’s HRQoL should focus more on family-related factors.…”
Section: Introductionmentioning
confidence: 99%